Influence of target gene mutations on survival, stage and histology in sporadic microsatellite unstable colon cancers - Jung, Barbara (2006)
High-frequency microsatellite unstable (MSI-H) colon tumors develop as a consequence of mutations at repetitive sequences in target genes. TGFBR2 and ACVR2, encoding TGFb superfamily receptors, and the proapoptotic gene BAX are frequent targets for frameshift mutation. We analyzed the effect of these mutations on survival and histology in 2 separate cohorts. Forty-eight MSI-H Dukes B2 colon tumors from a cohort of 172 patients had mutations in TGFBR2, BAX and ACVR2 correlated with patient survival. Further, 54 population-based MSI-H colon cancers of all stages from a cohort of 503 patients had mutations correlated with tumor stage, grade and size. Of 44 amplifiable MSI-H Dukes B2 tumors, 70% harbored TGFBR2, 63% BAX and only 4.5% ACVR2 mutations. While mutation alone did not influence survival, concomitant mutation of TGFBR2 and BAX was associated with an improved prognosis in Dukes B2 patients (p = 0.05). ACVR2 mutations were more frequent in the second, population-based cohort (stage II: 32.5%, p < 0.05). While no target gene mutation correlated with stage in this cohort, poor histological grade and large tumor volume were associated with mutant ACVR2, but not TGFBR2 or BAX mutations, and likely accounts for the lower prevalence of ACVR2 mutations in the first, well-differentiated Dukes B2 cohort. Because target gene mutations did not correlate with stage, they likely occur early in the pathogenesis of MSI-H cancers. Mutations in TGFBR2 and BAX may improve survival in MSI-H Dukes B2 patients, and mutations of ACVR2 may augment histological changes consistent with poor tumor grade that is characteristic of MSI-H colon cancers, and increase tumor size.